Security through Obscurity: A Critical Reassessment and Strategic Framework for Contemporary Cyber Defense - Madhuri Desaraju (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Security via obscurity (STO) has customarily encountered skepticism within cybersecurity circles, which frequently censure it for depending on secrecy instead of sturdiness. Nevertheless, developing threat environments reveal that calculated obscurity can play a vital role in further improving resilience as well as response effectiveness if integrated appropriately into broader defense strategies. This analysis shall further reexamine STO as a defined tactical layer within the scope of modern cybersecurity frameworks. A systematic, fact-based tactic toward its utilization is suggested. Empirical outcomes gauge the capability of a specific framework that actualizes obfuscation in system designs, which we put forward. STO does indeed considerably augment adversarial workload, better detection opportunities, and postpones exploitation, thus strengthening overall cyber defense postures, which the findings do show is not adequate by itself.